2019
DOI: 10.1039/c9nj00097f
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous 3D network Ce-doped NiO nanoflakes as high performance electrodes for supercapacitor applications

Abstract: In the present study, pristine NiO- and Ce (0.5, 1.0, 1.5, and 2%)-doped NiO nanoflakes were synthesised using the sol–gel method for supercapacitor applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…The above-mentioned observations suggest that Ce 3+ ions (with ionic radius 114 pm) have substituted Co 3+ ions (ionic radius 63 pm). 33,38 Further doping of Ce, that is, 7.0 at. % failed to reveal any further change in diffracted peaks suggesting that the optimum concentration of Ce for doping in Co 3 O 4 crystal lattice is upto 5.0 at.…”
Section: Xrd Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The above-mentioned observations suggest that Ce 3+ ions (with ionic radius 114 pm) have substituted Co 3+ ions (ionic radius 63 pm). 33,38 Further doping of Ce, that is, 7.0 at. % failed to reveal any further change in diffracted peaks suggesting that the optimum concentration of Ce for doping in Co 3 O 4 crystal lattice is upto 5.0 at.…”
Section: Xrd Analysismentioning
confidence: 99%
“…Due to this characteristic, Ce can be used as a dopant to advance the electrochemical properties of some TMOs/hydroxides. 5,33,34 They also observed that conductivity of manganese oxide was significantly enhanced due to doping of cerium ions. Moreover, the appropriate doping of cerium atoms has modified the morphology of manganese oxide particles resulting into shortening of ions transportation path, which provided much better conductivity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ni 0.95 Co 0.025 Mn 0.025 O 1−δ showed a specific capacitance of 673.33 F g −1 at a current density of 0.5 A g −1 [19]. Ce-doped NiO nanoflakes were synthesized by sol-gel method and they exhibited a specific capacitance of 2444 F g −1 which is three times that of the pure NiO materials [20]. La 3+ -doped NiO microspheres with porous structure was prepared simple hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide is an interesting transition metal oxide due to its chemical stability, abundance and wide applications in optical and electronic devices making it the best t for wide application, 13 but its poor electric conductivity and high resistance limits its use as electrode material. [14][15][16] To overcome this problem, a principle approach is to tailor the morphology in order to enhance the surface area of ZnO. It is well known that high surface area improves the chargetransfer capability and enriches the interaction of electrolyte with the electrode surface thus enhancing the diffusion of ions.…”
Section: Introductionmentioning
confidence: 99%